Online detection of Botnets on Network Flows using Stream Mining - Costa, Victor G. Turrisi da; Zarpelão, Bruno Bogaz; Miani, Rodrigo Sanches; Barbon Junior, Sylvio (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2018: Anais do XXXVI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2018.2418, 2018)
The threat posed by botnets of infecting a large number of devices and using them together to perform several malicious actions has become a growing issue to the Internet security. One way to deal with it is to have methods able to correctly identify those botnets and then run necessary countermeasures. Many approaches using machine learning (ML) have been proposed over the years to cope with botnet detection. Nonetheless, the algorithms commonly employed cannot adapt to new data without significant effort. In this sense, a ML research topic referred to as stream mining may be a solution. Stream mining algorithms are specially tailored to learn incrementally with new instances, without consuming significant memory or time. This work proposes an approach using the Very Fast Decision Tree, a classification algorithm used on stream mining that can learn incrementally when needed, to identify botnets by observing network flows. When evaluating the approach on multiple scenarios with different botnets, we were able to achieve high performance metrics on the majority of scenarios, while using a significantly low number of labelled instances.